The Representation of the Concept of “Power” in Modern English-Language Media (Eurasian Journal of Philology Science and Education, 2025)
This article analyzes the concept of “Power” as a multifaceted phenomenon in news of the modern English-language media. The relevance of the study is due to the fact that the mass media do not only reflect, but also shape the public perception of power, as well as the insufficient study of the concept of “Power” in the modern English-language media within the framework of the linguacognitive approach. The aim of the article is to identify the conceptual and linguistic characteristics of the concept of “Power” based on conceptual (conceptual-definitional and conceptual-contextual) and linguastylistic analysis. The result of the study is the semantic and cognitive aspect of the content of the concept of “Power” through linguistic means in BBC.com, The Guardian, CNN. The analysis shows that in the modern English-language media, the content of the concept of “Power” is often associated with coverage of political and social events in the country, decisions made, the purpose of the policy pursued by the country’s leadership.The theoretical and practical value of the study is that the analysis of the concept of “Power” expands its representation in cognitive models and language representation used in the English-language media, which leads to the possibility of using it in courses on cognitive linguistics, text and discourse analysis.Keywords: cognitive linguistics, concept, power, meaning, representation.